Solución de un problema de valor inicial - Oviedo-Ugalde, Norberto Gerardo (My University, 2018)
El video comprende la explicación de ejercicio en el cual se verifica que una cierta función y(x) la cual involucra una integral de 0 a x bajo una condición inicial dada, satisface una ecuación diferencial. Para la comprobación deriva la función dada y asimismo usa el teorema fundamental de cálculo, posteriormente se comprueba satisface el PVI al sustituir en la ecuación diferencial dada junto con la condición inicial.

The video includes the exercise explanation in which it is verified that a certain function y (x) which involves an integral from 0 to x under a given initial condition, satisfies a differential equation. For the verification derives the given function and also uses the fundamental theorem of calculation, later it is verified satisfies the PVI when substituting in the given differential equation along with the initial condition.
Keywords: Valores; Ecuaciones diferenciales; Soluciones; Teoremas; Cálculo; Matemáticas; Values; Differential equations; Solutions; Theorems; Calculation; Mathematics